Kontribusi Kepemimpinan Kepala Sekolah Melayani Terhadap Kinerja Guru SMK Negeri Bisnis Manajemen se Kota Padang - WENI ANGGRINA (Jurnal Bahana Manajemen Pendidikan, 2017)
The background of this study was the observation of the writer in Business ManagementSMK Padang which showed the performance of teachers is still less in line with expectations in the school. The researcher assumed that it wasrelated to servant leadership of the headmaster which is poor. This study was aimed to obtain information about the servant leadership of the headmaster and teacher performance in Management Business SMK Padang as well as determine the contribution of servant leadership of the headmastertowards teacher performance. This study was a correlational studydescribing the relationship between servant leadership of the headmasterand teacher performance in Management Business SMK Padang. The population of this study was all teachers in Management Business SMK Padang consist of158 people. The samples were56 people who wereselected by using proportional stratified random sampling technique. The instrument used for this study was tested by using Likert Scale questionnaire models. The questionnaire was tested to 10 respondents who were not the samples of this study to measure the validity and reliability of the questionnaire. The hyphothesis was tested by using Simple Regression analysis, Product Moment formula, r test and t test, while r2 was used to see the contribution of the headmaster leadership towards teachers’ performance. The findings of this study showed that the servant leadership was Good in category and the teacher performance was Good. The contribution of the servant leadership of the headmaster towards teachers’ performance was 29,16 %, while the other 70,84% was affected by other factors.